Peran Bimbingan Karier Vokasional terhadap Kesiapan Kerja Siswa SMK Muhammadiyah Sumowono - Fatmawati, Sri; Khotimah, Ika Khusnul; Miftakhudin, Miftakhudin; Kuat, Tri (Indo-MathEdu Intellectuals Journal, 2026)
Work readiness is a key competency that vocational high school graduates must possess in order to compete in an increasingly dynamic labor market. However, in practice, many vocational students still experience career confusion, limited career planning, and insufficient understanding of workplace demands. This study aims to describe the role of vocational career guidance in enhancing students’ work readiness at SMK Muhammadiyah Sumowono. The study employed a qualitative descriptive approach involving students, guidance and counseling teachers, and school management as research participants. Data were collected through in-depth interviews, observations, and documentation, while data credibility was ensured through source and technique triangulation. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that vocational career guidance plays an important role in helping students recognize their potential, understand the world of work, and develop more realistic career plans. Nevertheless, the implementation of career guidance faces several challenges, such as limited service time, varying levels of student motivation, and minimal involvement of industry partners. This study concludes that vocational career guidance has a strategic contribution to improving students’ work readiness and should be strengthened through collaboration among schools, parents, and industry